TEACHERS’ PERCEPTIONS ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION AT EX-RSBI PUBLIC JUNIOR SECONDARY SCHOOLS IN MAKSSAR - Fortuna, Nurkhaira Ariendita; Baa, Sultan; Sakkir, Geminastiti (Universitas Negeri Makassar, 2023)
The objectives of this research were to find out (1) the difference between teaching and learning using English at the RSBI program and Merdeka curriculum (2) the teachers’ perceptions on which program more enhances students’ English development and academic content (3) the teachers’ suggestions on the use of EMI (teaching Science and Math using English). This research applied descriptive qualitative research design. Interviews and documentation were used as the instruments to collect data. The participants of this research were five teachers from SMP Negeri 6 Makassar and SMP Negeri 12 Makassar. The participants were all Mathematics and Science teachers and had experienced the RSBI program. The results of the research showed: (1) students' competitive attitudes have decreased and the intensity of using EMI has decreased since the RSBI program was abolished, (2) there has been a decline in students' academic achievement and schools’ performance compared to when the RSBI program was still ongoing, (3) teachers' commitment, developing an ELT policy and re-programming bilingual classes are suggested to infuse the use of EMI into classroom pedagogy.